Nostalgia Value Of Viral Restaurants: The Importance Of Human Atmosphere and Perceived Value On Intention To Return - Oktavian ANP, Ramadhan (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
Viral restaurants are indeed on the rise, but many of them struggle to maintain longevity. A common issue is their focus on the viral aspect instead of understanding and catering to consumer needs. Interestingly, nostalgia can serve as a powerful marketing tool; it evokes a sense of comfort and helps consumers recall joyful memories from the past. In a recent study involving 100 participants, both men and women, PLS analysis was employed to assess the data. The findings suggest that the feeling of nostalgia positively influences the overall atmosphere and perceived value in a dining experience. However, it's important to note that while nostalgia enriches the experience, it doesn't necessarily correlate with a consumer's desire to return.